Sunni Ḥadīth And Continuous Commentaries On The Eschatological Mahdī: A Literary Analysis - Muhammad Fawwaz Muhammad Yusoff; Mohd Yusuf Ismail (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Indexed by WOS/Scopus/ERA